High Performance Current Amplifier [TK7871.58.P4 G896 2006 f rb] [Microfiche 8561]. - Gu, Hock Chin (2006)
A high bandwidth class AB current amplifier by using few compensation resistor technique and current mirrors is presented and analyzed. The simulation results are obtained using TSpice tool using 0.35μm CMOS TSMC process, at 2.5V power supply. The amplifier utilizes Class AB amplifier topology to achieve high bandwidth.